Characteristics of the gut microbiome in esports players compared with those in physical education students and professional athletes - Kulecka, Maria; Fraczek, Barbara; Balabas, Aneta; Czarnowski, Paweł; Zeber-Lubecka, Natalia; Zapala, Barbara; Baginska, Katarzyna; Glowienka, Maria; Szot, Monika; Skorko, Maciek; Kluska, Anna; Piatkowska, Magdalena; et al. (Frontiers in Nutrition, 2023)
Esports is a category of competitive video games that, in many aspects, may be similar to traditional sports; however, the gut microbiota composition of players has not been yet studied. Here, we investigated the composition and function of the gut microbiota, as well as short chain fatty acids (SCFAs), and amino acids, in a group of 109 well-characterized Polish male esports players. The results were compared with two reference groups: 25 endurance athletes and 36 healthy students of physical education. DNA and metabolites isolated from fecal samples were analyzed using shotgun metagenomic sequencing and mass spectrometry, respectively. Physical activity and nutritional measures were evaluated by questionnaire. Although anthropometric, physical activity, and nutritional measures differentiated esports players from students, there were no differences in bacterial diversity, the Bacteroidetes/Firmicutes ratio, the composition of enterotype clusters, metagenome functional content, or SCFA concentrations. However, there were significant differences between esports players and students with respect to nine bacteria species and nine amino acids. By contrast, all of the above-mentioned measures differentiated professional athletes from esports players and students, with 45 bacteria differentiating professional athletes from the former and 31 from the latter. The only species differentiating all three experimental groups was Parabacteroides distasonis, showing the lowest and highest abundance in esports players and athletes, respectively. Our study confirms the marked impact of intense exercise training on gut microbial structure and function. Differences in lifestyle and dietary habits between esports players and physical education students appear to not have a major effect on the gut microbiota.